Current and Historical Application of Knowledge Management in Economy - Tomé, Eduardo (Ital Publication, 2020)
Objectives: The paper tries to analyse the current and historical application of Knowledge Management in the Portuguese Economy, particularly since the democratic revolution of 1974. Methods/Analysis: Study is based in theories about the impacts of knowledge in countries at a micro and a macro scale. A three levels mode is used, related to context (namely 1) Historical background; 2) basic economic and social data: 3) broad vocational education and training (VET) systems; 4) institutional actors; 5) political context), intervention (namely 1) basic legislative documents, 2) guidelines on eligibility, 3) programs, 4) evaluation procedures) and outcomes (namely 1) stocks, investment, and outcomes; 2) price, quantity, supply, demand, equilibria; 3) needs). Data used are statistical published data and other published documents. Findings: The context changed for the better, because after 1974 the country rulers installed a regime in which knowledge was not seen like a luxury but as a basic need; the change in context was also helped by the adhesion to the EU, which in turn led to massive interventions supported by funds like the ESF and the Regional fund; as a result outcomes are finally seen, as the increase in supply and demand of knowledge and also in the income and employability of the Portuguese attests. Novelty/Improvement These findings are important because they depict the slow but sure transformation of Portugal into a Knowledge Economy. Should be complemented by a more detailed analysis, with a larger group of researchers. Doi: 10.28991/esj-2020-01245 Full Text: PDF